A Huge Capital Drop with Compression of Femoral Vessels Associated with Hip Osteoarthritis - Tomoya Takasago; Tomohiro Goto; Takahiko Tsutsui; Kenji Kondo; Daisuke Hamada; Ichiro Tonogai; Keizo Wada; Koichi Sairyo (Case Reports in Orthopedics)
A capital drop is a type of osteophyte at the inferomedial portion of the femoral head commonly observed in hip osteoarthritis (OA), secondary to developmental dysplasia. Capital drop itself is typically asymptomatic; however, symptoms can appear secondary to impinge against the acetabulum or to irritation of the surrounding tissues, such as nerves, vessels, and tendons. We present here a case of unilateral leg edema in a patient with hip OA, caused by a huge bone mass occurring at the inferomedial portion of the femoral head that compressed the femoral vessels. We diagnosed this bone mass as a capital drop secondary to hip OA after confirming that the mass occurred at least after the age of 63 years based on a previous X-ray. We performed early resection and total hip arthroplasty since the patient’s hip pain was due to both advanced hip OA and compression of the femoral vessels; moreover, we aimed to prevent venous thrombosis secondary to vascular compression considering the advanced age and the potent risk of thrombosis in the patient. A large capital drop should be considered as a cause of vascular compression in cases of unilateral leg edema in OA patients.